Internal Structure Characteristics and Formation Mechanism of Reverse Fault in the Carbonate Rock, A Case Study of Outcrops in Xike’er Area, Tarim Basin, Northwest China - Geng, Feng; Wang, Haixue; Hao, Jianlong; Gao, Pengbo (Frontiers in Earth Science, 2021)
China's Paleozoic deep carbonate effective reservoirs, mainly non-porous reservoirs, are generally formed under the interaction of late diagenesis, hydrothermal fluids, and structural fractures. Faults and their deformation mechanism and internal structure of fault zones play an important role in the formation of carbonate reservoirs and hydrocarbon accumulation. Based on the detailed analysis of outcrop data in Xike’er, Tarim Basin, this paper systematically studies the deformation mechanism and internal structure of thrust fault zone in carbonate rock area, and discusses the reservoir characteristics, control factors and development rules. The study shows that the deformation mechanism of the fault in carbonate rocks is faulting and fracturing, and the dual structure of fault core and damage zone is developed. The fault core is mainly composed of fault breccia, fault gouge and calcite zone, and a large number of fractures are formed in the damage zone, which are cemented by calcite locally. The mineral composition and rare earth element tests show that the fault core has the dual effect of hydrothermal fluids and atmospheric fresh water, which is easy to be cemented by calcite; while the damage zone is dominated by atmospheric fresh water, which is a favorable zone for the development of fracture vuggy reservoirs. Therefore, the damage zone is the "sweet spot" area of carbonate oil and gas enrichment, and generally shows strip distribution along the fault.